Law, Borders and the Territorialisation of Cyberspace - Tsaugourias, Nicholas (UI Scholars Hub, 2018)
This article explores the relationship between law and more specifically international law with territory and borders and how this relationship manifests itself in cyberspace. It claims that it manifests itself through two processes: a process of territorialisation of cyberspace that is, the application of territorial notions of international law to persons, activities, and objects existing or operating in or through cyberspace and, secondly, in States asserting their sovereignty in cyberspace by creating national cyberspace zones. All in all, its main claim is that borders are still relevant in the legal regulation of cyberspace